2021
DOI: 10.3390/ijerph18126375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Air Pollution (PM2.5) on Child Mortality: Evidence from Sixteen Asian Countries

Abstract: Air pollution in Asian countries represents one of the biggest health threats given the varied levels of economic and population growth in the recent past. The quantification of air pollution (PM2.5) vis à vis health problems has important policy implications in tackling its health effects. This paper investigates the relationship between air pollution (PM2.5) and child mortality in sixteen Asian countries using panel data from 2000 to 2017. We adopt a two-stage least squares approach that exploits variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…For example, one study by Egondi et al indicated that exposure to elevated levels of PM 2.5 was associated with a high mortality rate among children ( Egondi et al, 2018 ). Another study by Anwar et al investigated the relationship between PM 2.5 and child mortality using the least square method, and found that a one unit increase in annual PM 2.5 concentration was associated with a 14.5% increase in U5MR ( Anwar et al, 2021 ). In the present study, we applied a Bayesian inference approach, which takes prior parameter information into account, and as such is a more flexible method to illuminate the relationship ( Elster and Wübbeler, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study by Egondi et al indicated that exposure to elevated levels of PM 2.5 was associated with a high mortality rate among children ( Egondi et al, 2018 ). Another study by Anwar et al investigated the relationship between PM 2.5 and child mortality using the least square method, and found that a one unit increase in annual PM 2.5 concentration was associated with a 14.5% increase in U5MR ( Anwar et al, 2021 ). In the present study, we applied a Bayesian inference approach, which takes prior parameter information into account, and as such is a more flexible method to illuminate the relationship ( Elster and Wübbeler, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned crucial determinants, ambient particulate matter pollution has been identified as a potential preventable risk factor of various health outcomes ( Yu, 2020 , Zhang et al, 2020 , He et al, 2022 ). For instance, one study by Anwar investigated the impact of PM 2.5 on child mortality, and found that a single unit increase in PM 2.5 leads to an increase of 14.5 in U5MR ( Anwar et al, 2021 ). Yitzhaks et al estimated that each 3 µg/m 3 increase in ambient PM 2.5 was associated with an increase of 4.4% in all-cause mortality ( Yitshak-Sade et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing economic activities, along with an increase in energy consumption, leads to deterioration in environmental quality. The worsening environmental quality in terms of air pollution and severe weather conditions poses a great threat to human lives as almost 99% of the worlds’ population lives in areas with air quality levels that already exceed WHO limits [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rising trends of the PM2. 5, it has been identified as a major public health hazard for the people of Bangladesh, especially in the urban and semi-urban areas (Rahman et al 2019). The high PM2.5 standard threshold also has significant impacts on vulnerable demographic groups, especially for pregnant women, children, and elderly (over the age of 60) residents (Miller and Xu 2018).…”
Section: Introductionmentioning
confidence: 99%
“…found that in Nairobi (Kenya), child mortality is higher in regions with poor economic conditions and high air pollutions areas irrelevant of gender. The national panel child mortality and PM2.5 data and their statistical relationship from 16 Asian countries revealed that R 2 values were 0.75 and 0.87 in WHO and World Bank datasets, respectively(Anwar et al 2021). Daily mortality increases when the concentration of PM2.5 increases which was found by a pooled concentration-response analysis conducted in 652 cities in the world(Liu et al 2020).…”
mentioning
confidence: 99%